Genetic Variability and Trait Correlations of Melon (Cucumis melo L.) Genotypes - Heru Anggara; Dicky Marsadi; Listihani Listihani (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2025)
Melon (Cucumis melo L.) is an important horticultural crop. Melon breeding programs require comprehensive information on genetic variability and selection-related traits. Genetic variability and correlations among plant characters are essential parameters for effective selection in the S2 Population. This study aimed to evaluate the genetic variability of several melon genotypes and to analyze correlations among plant characters as a basis for selection. The experiment was conducted using fourteen melon genotypes derived from selfed populations at the S₂ generation. The study employed a randomized complete block design with a single factor, consisting of 14 S₂ melon genotypes and four replications. The experimental unit is one individual plant in a polybag. The Observations of qualitative traits indicated the presence of variation within the genotypes for fruit rind color and fruit flesh color. Genotypes G2 exhibited the greatest fruit length (13.47 cm) and fruit diameter (11.95 cm). Genotypes G15 showed the highest total soluble solids content (150 Brix), while genotypes G7 had the thickest fruit flesh (3.25 cm). Broad-sense heritability estimates of the observed traits ranged from low to moderate. The traits of fruit length, fruit diameter, and fruit weight exhibited moderate broad-sense heritability (>45%). They were positively and significantly correlated with fruit weight, indicating that these traits can be used as selection criteria for fruit weight in subsequent plant breeding programs.